Microstructure evolution and mechanical/physical properties of 25# valve alloys steel subjected to deep cryogenic treatment. (February 2019) - Liu, Xiao; Zhao, Chunfang; Zhao, Kang
Abstract: In this work, 25# valves alloy steel was selected as the experimental material for the new generation of low temperature valves steel. Effect of deep cryogenic treatment (DCT) time and cycle number on the microstructure evolution and mechanical/physical properties of 25# alloys steel were investigated and analyzed. Experimental results show that the microstructure for the tiny lath martensite after quenching, also lamellar martensite and retained austenite were obtained after DCT. At the same time, the retained austenite transformed into tiny lath martensite microstructure. Also, the smaller dispersion of M6 C carbides were precipitated and distributed in grain boundaries and thin film retained austenite with an increase of DCT time and cycles as well as formation of stacking faults. The cryogenic processing has an obvious impact on the mechanical properties of materials. The strength of the material increases firstly and then sharply decreases with DCT time and cycles number, but the strain exhibits the opposite trend. The maximum strength is 1390 MPa, which is triple the original sample with a value of 441 MPa. Also, the hardness of the materials increases remarkably with a value of 52.6 HRC, enhancement of ∼28.9% and then decreases slightly with an increase of DCT time and cycles number. The fracture mechanism is typical cup - cone - shaped ductile fracture. After DCT, the linear expansion coefficient of the material gradually decreases and then table, which is satisfied with the cryogenic valves steel at low temperature service conditions. Highlights: M6 C carbides were precipitated and distributed in thin film retained austenite as well as formation of stacking faults. The maximum strength is 1390 MPa, which are triple the original sample. Hardness of the materials increases remarkably with a value of 52.6 HRC, enhancement of ∼28.9%. The fracture mechanism is typical of cup - cone - shaped ductile fracture.